Dorothy Hartley - Wondrausch, Mary (Petits Propos Culinaires, 2024)
Dorothy Hartley’s book Food in England, the republication of which this year is celebrated on page 51, is perceived by many to be the greatest single contribution which has ever been made to English food history, if by that phrase is meant the history of the food eaten in rural England in the past. Now, more than ten years since her death, it is very good news that the author of this short essay is working on a full biography of Dorothy Hartley, taking in the other aspects of her life’s work as well as her pioneering contribution to English food history. Like Dorothy Hartley, Mary Wondrausch is a woman of many talents and many activities. We are grateful to her for responding to our invitation to tell our readers something about Dorothy Hartley’s life, so that our review of her book can be seen in a biographical context.